Training on Using Mendeley for Citations in Writing Scientific Papers for Students - Wahyuddin; Syafaruddin; Maharida (Jurnal Pengabdian Masyarakat Bestari, 2022)
As an effort to develop science and technology and increase the nation's competitiveness, performance in the form of scientific publications is mandatory for students. Therefore, training is carried out on using Mendeley for citations in writing scientific papers with the aim of increasing students' understanding and skills in making citations and compiling a bibliography in writing scientific papers. The results of the activity concluded that training on using Mendeley for citations in writing scientific papers for students can improve students' understanding and skills in making citations and compiling a bibliography in writing scientific papers.